Improving and Boosting Higher Education Competitiveness: Assessment, Ranking, and Analysis using TreeSoft Set - Liang Zhao (Neutrosophic Sets and Systems)
Higher education competitiveness has become a crucial factor in determining the global standing of universities and colleges. With rapid advancements in technology, globalization, and the evolving job market, institutions must continuously adapt to enhance their academic offerings, research output, and industry collaborations. This paper explores the key factors influencing higher education competitiveness, including academic excellence, infrastructure, internationalization, financial stability, industry partnerships, and student satisfaction. By employing a multi-criteria decision-making (MCDM) approach, this study evaluates and ranks higher education institutions based on these essential criteria. Two MCDM methods are used in this study such as CIMAS methodology to compute the criteria weights and the WASPAS methodology to rank the alternatives. We used the TreeSoft set to deal with different criteria and sub-criteria by dividing the criteria and sub-criteria into a Tree to obtain the relations.